Morphology of the digestive tube of Macuxitermes triceratops and its phylogenetic implications (Isoptera: Termitidae: Nasutitermitinae) - Constantino, R. [UNESP] (California State University, 1997)
The gross morphology of digestive tube of Macuxitermes triceratops is described and illustrated. The gut of this species is very similar to those of Embiratermes and Ibitermes, and does not show any obvious autopomorphic character. The phylogenetic relations of this genus are discussed based on the available evidence, and it is concluded that it is probably the sister group of Armitermes + Curvitermes + Cryilliotermes.